What are the biggest obstacles to growth of SMEs in developing countries? - A picture emerging from an enterprise survey - Yao Wang (Charles University in Prague, Institute of Economic Studies (IES), 2016)
SMEs are drivers of economic growth and job creation in developing countries. It is paramount to determine the factors that hinder their growth. This paper uses the Enterprise Survey from the World Bank which covers data from 119 developing countries to investigate the biggest obstacles SMEs are confronting and the determinants that influence the obstacles as perceived by enterprise managers. The results show that SMEs perceive access to finance as the most significant obstacle which hinders their growth. The key determinants among firms' characteristics are size, age and growth rate of firms as well as the ownership of the firm. The latter – the role of the state in financing SME - is particularly intriguing. External reasons for the financing dilemma are also examined. It is shown that the main barriers to external financing are high costs of borrowing and a lack of consultant support.
Keywords: 330; SMEs; Obstacles to Growth; Financing Dilemma; Developing Countries; firm characteristics; internal and external barriers